PENGARUH GAYA KEPEMIMPINAN DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN PEMERINTAH KOTA MEDAN - Erlando Purba; Marudut Sianturi; Dearlina Sinaga (JURNAL PROINTEGRITA, 2019)
Working performance can be influenced by several factors, such as leadership style and working motivation. Leadership style determines the employee performance since the leader has the authority to direct his/her subordinates in carrying out organizational tasks. Thus, the work motivation may also affect employee performance, for in its absence, the poor of employees working enthusiasm tend to ignore their tasks.The purpose of this study is to determine the effect of leadership style on employees performance, the effect of working motivation and simultaneously the effect of leadership style and working motivation on the employees performance of Dinas Perhubungan Pemerintah Kota Medan Officers.Population of this study are 474 officers of Dinas Perhubungan Pemerintah Kota Medan. The number of sample are 83 officer, determinated by using Slovin formula. The techniques of data collecting are questionnaires, interviews and documentation studies. While data analysis technique used are classic assumption test, multiple regression, t-test, F-test and coefficient of determination. The results showed that the leadership style variable partially has a positive and significant effect on the employees performance. The better the leadership style, the higher the employee's performance. The working motivation variable partially has a positive and significant effect on employees performance. The better the working motivation, the higher the employee's performance. Both leadership style and work spirit variables simultaneously have a significant effect on employees performance. Mostly (67.20%) of employees performance variation can be explained by leadership style and work spirit simultaneously, while the remaining 32.80% is explained by other factors, such as competency and working discipline variables. It is recommended that the Head of Dinas Perhubungan Pemerinah Kota Medan need to improve his leadership in term of democratic style, which gives the authority of employees to make decisions on their respective fields of work, as well as avoiding relationships outside of work with subordinates. The Head of the Dinas Perhubungan Pemerinah Kota Medan should improve the employees’ working motivation by implementing working ethics to increase working attendance, as well as applying the positive motivation for higher working enthusiasm by giving awards to outstanding employees.